The accuracy of alternative GDP growth forecasts: Do they represent a credible alternative to the official ones? - Jiří Šindelář (Review of Economic Perspectives, 2015)
The paper deals with the accuracy of the real GDP growth forecasts produced by two Czech non-governmental institutions: the Czech-Moravian Confederation of Trade Unions (CMKOS) and the Czech Banking Association (CBA) in the years 2007-2014 and 2011-2014 respectively. Utilizing a research method composed of simple (AFE), scale-dependent (RMSE) as well as relative (MASE) error measures, we found out that (i) CMKOS predictions achieved a lower forecasting error on average, beginning with a notable overestimation in the first turnover point from growth to decline (2008-2009), yet followed by gradual improvement resulting in superior accuracy over set benchmarks (Ministry of Finance, Czech National Bank, OECD) in later years (2010-2014). The CBA predictions, on the other hand, exhibited (ii) a high level of interconnection with official bodies (MF, CNB), but with overall inferior forecasting accuracy, despite the shorter time frame (2011-2014). Overall, the study suggests that of the two surveyed non-governmental bodies, only CMKOS forecasts represent a viable alternative to the official predictions published by the Ministry of Finance or the Czech National Bank, as CBA forecasts were found to be a less accurate satellite of these bodies.
Keywords: 330